Fossil Hemerobiidae (Neuroptera) from the Eocene Tadushi Formation, the Russian Far East, with description of a new genus - Makarkin, Vladimir N. (Zootaxa, 2023)
Three specimens of Hemerobiidae (Neuroptera) are described from the early/middle Eocene Tadushi Formation of the Russian Far East. They clearly belong to three species, but only one can be named, Archibaldia aristovi gen. et sp. nov.; the other two are fragmentary and treated as genus and species A and B. The new genus also includes A. wehri (Makarkin), comb. nov. from the early Eocene of western North America. The forewing venation of Archibaldia gen. nov. is most similar to that of the Eocene genus Proneuronema Makarkin et al., but differs from it and other genera of the family by the following character states: the basal crossvein 1r-m is present; crossveins between RA and RP1/RP2 are present; RP1 has anteriorly directed pectinate branches; M is dichotomously branched; CuP is forked proximad the first gradate series; and there are crossveins between branches of CuP. The presence of the basal crossvein 1r-m separates Archibaldia gen. nov. from all other hemerobiids and is here interpreted as an autapomorphy of the genus.